2008
DOI: 10.1128/jvi.01736-07
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Genetics and Proteomics To Identify Aphid Proteins Associated with Vector-Specific Transmission of Polerovirus ( Luteoviridae )

Abstract: Cereal yellow dwarf virus-RPV (CYDV-RPV) is transmitted specifically by the aphids Rhopalosiphum padi andSchizaphis graminum in a circulative nonpropagative manner. The high level of vector specificity results from the vector aphids having the functional components of the receptor-mediated endocytotic pathways to allow virus to transverse the gut and salivary tissues. Studies of F 2 progeny from crosses of vector and nonvector genotypes of S. graminum showed that virus transmission efficiency is a heritable tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 34 publications
5
76
0
1
Order By: Relevance
“…For example, incorporation of cyclophilin A into the newly synthesized human immunodeficiency virus 1 (HIV-1) particles is required for virion attachment to host cells (64), while its recruitment by the GAG polyprotein during HIV-1 infection (11) promotes HIV-1 replication (12). Cyclophilins were identified in greenbugs (Schizaphis graminum) that are vectors of Cereal yellow dwarf virus (family Luteoviridae) but not in nonvectors of the same aphid species (85). Two different proteins coresolved within spot 283, the protein yellow-like and 26S protease regulatory subunit 7, which have been associated with melanization and behavior of D. melanogaster (22,83) and the ATP-dependent degradation of ubiquitinated proteins (14), respectively.…”
Section: Figmentioning
confidence: 99%
“…For example, incorporation of cyclophilin A into the newly synthesized human immunodeficiency virus 1 (HIV-1) particles is required for virion attachment to host cells (64), while its recruitment by the GAG polyprotein during HIV-1 infection (11) promotes HIV-1 replication (12). Cyclophilins were identified in greenbugs (Schizaphis graminum) that are vectors of Cereal yellow dwarf virus (family Luteoviridae) but not in nonvectors of the same aphid species (85). Two different proteins coresolved within spot 283, the protein yellow-like and 26S protease regulatory subunit 7, which have been associated with melanization and behavior of D. melanogaster (22,83) and the ATP-dependent degradation of ubiquitinated proteins (14), respectively.…”
Section: Figmentioning
confidence: 99%
“…We combined genetics and proteomics to identify several proteins in S. graminum that interact with and/or direct the movement of Cereal yellow dwarf virus-RPV (CYDV-RPV) along the circulative transmission pathway (77). That study demonstrated the discovery potential of the F2 population for revealing proteins involved in virus circulative transmission.…”
mentioning
confidence: 99%
“…Aphid soluble proteins were extracted from mixed developmental stages by homogenizing the tissues in liquid N 2 using a mortar and pestle. An extraction buffer (50 mM Tris-HCl, pH 7.5, and 150 mM NaCl) was added to the aphid powder at a ratio of 1 mL of buffer to 1 g of aphids and frozen overnight (Yang et al, 2008). After centrifugation at 13,000g for 30 min, at 4°C, the supernatant was used for assays after adjusting the protein concentration to 1 mg/mL as determined with a Bradford assay using bovine serum albumin as a standard.…”
Section: Aphid Saliva Collection and Protein Extractionmentioning
confidence: 99%